Depiction of a Surasundari (celestial damsel) - Temples of India Project Team (Jio Institute, 2024)
On the northern wall, there is a depiction of a surasundari (celestial damsel) an elaborate hairdo, fashioned into a bun. She stands tall and slender, bedecked with substantial jewellery. One of her hands is fractured, while the other rests near her exposed reproductive organ. It is worth noticing that both ascetic and surasundari are shown with their revealed genitalia, they both represent different natures and stand for opposite symbolism.